Case Series on Depigmentation - Talati, Meenakshi; Prithyani, Saurabh; Mitra, Dipika; Shah, Rohit; Rodrigues, Silvia; Vijayakar, Harshad (International Journal For Research In Health Sciences And Nursing, 2018)
Gingival pigmentation is a major concern for a large number of patients visiting the dentist. The patients with excessive gingival display and pigmentation are more concerned esthetically. Most pigmentation is caused by five primary pigments out of which melanin has the maximum incidence rate. Melanin hyper pigmentation usually does not present as a medical problem, but patients may complain about their unesthetic black gums. The gingiva is the most frequently pigmented intraoral tissue, with the highest rate observed in the area of the incisors Esthetic periodontal plastic surgery is a boon in patients having “dark gums” and “gummy smile.” This article offers a retrospective case series of gingival depigmentation by epithelial excision using scalpel. Out of the several techniques employed for depigmentation, the surgical technique using scalpel is still the first and most popular technique. This is a case report representing a simple surgical technique of de‑epithelization which has been successfully used to treat gingival hyperpigmentation caused by excessive melanin deposition and highlights the relevance of an esthetically pleasing smile especially in smile conscious individuals.